Effect of PAI-1 Levels on the Molar Concentrations of Active Tissue Plasminogen Activator (t-PA) and t-PA/PAI-1 Complex in Plasma - Chandler, Wayne L.; Trimble, Sara L.; Loo, Swee-Chin; Mornin, Dan (Blood, 1990)
We determined the in vivo molar concentrations of active tissue plasminogen activator (t-PA), active plasminogen activator inhibitor type 1 (PAI-1), and t-PA/PAI-1 complex. t-PA activity was measured in plasma stabilized by immediate acidification. PAI-1 activity and t-PA/PAI-1 complex antigen were measured in citrated plasma; these measurements were corrected for the loss in PAI-1 activity and increase in complex that occurs in unacidified plasma samples due to the continued reaction between t-PA and PAI-1 after the sample was drawn. To convert t-PA and PAI-1 activity measurements into molar concentrations we determined the specific molar activity of t-PA and PAI-1 in vivo: 4.48 x 1013 lU/mol. Of 72 subjects studied, 13 had less than 150 pmol/L active PAI-1; in these individuals 33% ± 21 % of their t-PA was active and the molar ratio of active t-PA to active PAI-1 was 0.20 ± 0.13. In the 11 subjects with greater than 500 pmol/L active PAI-1, 1.5% ± 1.1 % of the t-PA was active and the molar ratio of active t-PA to active PAI-1 was 0.0043 ± 0.0036. Overall, the fraction of active t-PA declined exponentially as a function of the active PAI-1 concentration. During the day, the percentage of total t-PA that was active increased from 12% at 8:00 AM to 31 % at 8:00 PM, while the molar ratio of active t-PA to active PAI-1 increased from 0.05 to 0.22 from morning to evenina (n = 12).